Quantifying age-related differences in diffusion tensor imaging biomarkers for the male urethral sphincter of prostate cancer patients - Verde, Ana Sofia de Castro (2019)
Tese de mestrado integrado, Engenharia Biomédica e Biofísica (Sinais e Imagens Médicas) Universidade de Lisboa, Faculdade de Ciências, 2019